Necessary functionality for electronic text active reading - Ibrahim, Nurulhuda; Othman, Azliza (Universiti Utara Malaysia, 2010)
Reading frequently involves not just looking at words on a page, but also underlining, highlighting and commenting, either on the text or in a separate notebook. Readers use these marks to organize their reading for later review and retrieval. This combination of reading with critical thinking and learning is called active reading. Active reading is a fundamental part of education and knowledge work and often requires readers to move from one text to another to satisfy their information needs.Lots of resources now are available in electronic or digital form and people can access and read plenty of information from Internet.Numerous software based readers with certain functionalities are made available to satisfy electronic reading requirement.However, these functionalities are diverse among readers. In addition, the functionalities provided are not ranked based on user needs.This study will define necessary functionalities for electronic text active reading.The research framework is divided into two major phases which are (i) identifying necessary functionalities based on available commercial software based readers, and (ii) identifying necessary functionalities based on reading walkthroughs, and user surveys and observations.The finding of this study may possibly contribute to design and development of electronic reading applications, by providing necessary functionalities for electronic reading.